Warren Buffett inside the ultimate money mind - Hagstrom, Robert G. 1956 (Wiley, 2021)
"Often described as the greatest investor of all time, Warren Buffett grew a $100 investment in the late 1950s into an investment empire, becoming in the process one of the most wealthy individuals in the world and the foremost authority on investing in our generation While it provides a solid foundation of Buffett's principles and his personal background for those who may be new to the Berkshire story, the core of the text moves in new and exciting directions. It is, in a very real sense, the culmination of years of studying the man so often described as the world's best investor"